Communal Livestock Farmers’ Perceptions of Foot-and-Mouth Disease Control Measures in Mopani District, Limpopo Province (Research in Agriculture Livestock and Fisheries, 2026)
Foot-and-mouth disease (FMD) poses a significant risk to livestock-dependent livelihoods in communal areas of South Africa, where effective management relies on farmer collaboration amid regular livestock movement and reliance on markets. This study analyzed the influence of communal farmers' perceptions of FMD risk and control measures on their reporting and compliance behaviors in the Mopani District of Limpopo Province, aiming to inform effective disease control strategies. A qualitative exploratory design was employed, using semi-structured questionnaires administered to 160 communal livestock farmers. Data were analyzed employing Braun and Clarke’s reflexive thematic analysis. Farmers identified significant FMD symptoms but hesitated to report them due to the associated quarantine measures and movement restrictions, resulting in severe livelihood losses. Farmers believed that vaccination and regular dip-tank inspections were effective ways to protect themselves against FMD. In contrast, quarantine and movement restrictions were perceived as shocks to livelihoods, disrupting sales and household cash flow. While information relied heavily on animal health technicians, the absence of acknowledgment and feedback after the farmer interaction frequently eroded trust in the official response. The results show that technically effective control programs can be socially dangerous if they do not adequately consider livelihood costs, procedural fairness, and two-way communication. Improving FMD control requires participatory risk governance, backed by reliable preventive services, established feedback mechanisms, effective risk communication, transparent and timely restrictions with consistent enforcement, and organized farmer engagement through dip-tank platforms.Res. Agric. Livest. Fish. Vol. 13, No. 1, April 2026: 117-131